Prevalence of symptoms of Raynaud's phenomenon in general practice. - Silman, A (1990)
OBJECTIVE--To investigate the prevalence of Raynaud's phenomenon in the populations of five general practices. DESIGN--Two populations studied. A questionnaire was given to all new patients attending five general practices over four weeks, and the same questionnaire was sent by post to a random sample of adults from two of the practices. SETTING--General practices in inner London, Merseyside, and Cheshire. SUBJECTS--1532 Patients who completed questionnaires (1119 who attended the surgeries (response rate unknown) and 413 respondents to the postal survey (response rate 69%)). MAIN OUTCOME MEASURES--Response to questionnaire on symptoms of Raynaud's phenomenon: patients were regarded as having the disease if they had episodes of blanching of the fingers that were precipitated by cold and accompanied by sensory symptoms (pins and needles or numbness). Subsequent interview and clinical appraisal of patients with the disease according to their responses to the questionnaire. RESULTS--The prevalence of Raynaud's phenomenon was 11% (26/231) and 19% (34/182) respectively in men and women who completed the postal questionnaire and 16% (56/357) and 21% (157/762) respectively in those who completed the questionnaire when attending their general practice. Thus the overall rates were slightly higher in women, but there was no effect of age even after adjustment of the rates for practice and method of survey. CONCLUSION--The prevalence of Raynaud's phenomenon is high compared with the low number of patients who seek treatment for the disease.